2017
DOI: 10.1186/s13073-017-0498-x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent de novo mutations in neurodevelopmental disorders: properties and clinical implications

Abstract: Next-generation sequencing (NGS) is now more accessible to clinicians and researchers. As a result, our understanding of the genetics of neurodevelopmental disorders (NDDs) has rapidly advanced over the past few years. NGS has led to the discovery of new NDD genes with an excess of recurrent de novo mutations (DNMs) when compared to controls. Development of large-scale databases of normal and disease variation has given rise to metrics exploring the relative tolerance of individual genes to human mutation. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
89
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(93 citation statements)
references
References 140 publications
(298 reference statements)
1
89
1
2
Order By: Relevance
“…Intellectual disability (ID) is a clinically heterogeneous cognitive disorder with an overall prevalence of approximately 1%–3% in the general population (Boyle et al., ; Iwase et al., ; Maulik, Mascarenhas, Mathers, Dua, & Saxena, ; Wilfert et al., ). The introduction of diagnostic whole exome sequencing (WES) has been particularly successful identifying autosomal dominant (AD) (de novo) causes for ID (de Ligt et al., ; Veltman & Brunner, ; Yang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Intellectual disability (ID) is a clinically heterogeneous cognitive disorder with an overall prevalence of approximately 1%–3% in the general population (Boyle et al., ; Iwase et al., ; Maulik, Mascarenhas, Mathers, Dua, & Saxena, ; Wilfert et al., ). The introduction of diagnostic whole exome sequencing (WES) has been particularly successful identifying autosomal dominant (AD) (de novo) causes for ID (de Ligt et al., ; Veltman & Brunner, ; Yang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, one potential systematic explanation is that BRSK2 is less deeply covered in exomes, and the observed enrichment, in part, reflects the effects of the genome sequencing that was used for the HudsonAlpha probands described here. It has been shown previously that genome sequencing provides better coverage, in general, over coding exons than exome sequencing does, 27,31,[33][34][35][36] and that some exons, including among clinically relevant genes, tend to be more poorly covered by exomes. 36 We find that BRSK2 is less well covered by exomes than by genomes in gnomAD (Figure 3).…”
mentioning
confidence: 99%
“…The identification of genes that are recurrently mutated across multiple disease individuals has been a major route to discover novel disease genes 69 . We identified recurrent variants within three fetal brain enhancer clusters associated with genes involved in nervous system development (CSMD1, OLFM1, POU3F3), and found that this enrichment was significant relative to expectations.…”
Section: Discussionmentioning
confidence: 99%